1995
DOI: 10.1007/bf00311684
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative disseminated intravascular coagulation (DIC) associated with aortic aneurysm ? does it need to be corrected before surgery?

Abstract: Disseminated intravascular coagulation (DIC) is one of the complications accompanying aortic aneurysm. We herein report four patients with aortic aneurysm who had DIC preoperatively. In all four cases, DIC was corrected immediately after surgery; however, in two cases, DIC could not be corrected preoperatively. This prompted us to reconsider the importance of correcting DIC before surgery. Of the four cases reported in this paper, DIC existed even at the time of surgery in two cases, in spite of meticulous tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In patients with DIC, local activation of coagulation results in the systemic depletion of coagulation factors and platelets, 1 and the basic principal for treating DIC is anticoagulation therapy, such as heparin. 7,8,11,12 Cummins et al reported that long-term treatment with LMWH could provide good symptomatic control of chronic DIC associated with AAA, 5 and as far as we could ascertain, there is not a great difference between LMWH and UFH. However, subcutaneous injection was ruled out because of the large purpura at the site of injection and so we needed to use a drug that could be administered as a bolus injection.…”
Section: Discussionmentioning
confidence: 60%
“…In patients with DIC, local activation of coagulation results in the systemic depletion of coagulation factors and platelets, 1 and the basic principal for treating DIC is anticoagulation therapy, such as heparin. 7,8,11,12 Cummins et al reported that long-term treatment with LMWH could provide good symptomatic control of chronic DIC associated with AAA, 5 and as far as we could ascertain, there is not a great difference between LMWH and UFH. However, subcutaneous injection was ruled out because of the large purpura at the site of injection and so we needed to use a drug that could be administered as a bolus injection.…”
Section: Discussionmentioning
confidence: 60%
“…Preoperative DIC is a severe complication; however, the therapeutic strategy in AAA with DIC remains controversial. 3,4) Since Fine et al 1) reported a case of consumptive coagulopathy of a dissected aneurysm in 1967, there have been many reports on AAA-associated coagulopathy. [2][3][4] Some reports indicate surgery for AAA enables correction of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Since Fine et al 1) reported a case of consumptive coagulopathy of a dissected aneurysm in 1967, there have been many reports on AAA-associated coagulopathy. [2][3][4] Some reports indicate surgery for AAA enables correction of thrombocytopenia. Oba et al 3) opinioned that surgeons should not expend an undue amount of time to correct DIC preoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations